Teachers’ Understandings of Critical and Higher Order Thinking and What This Means for Their Teaching and Assessments - Schulz, Henry W; FitzPatrick, Beverly (Alberta Journal of Educational Research, 2016)
Critical and higher order thinking is essential to education, but it is not clear what teachers understand this to mean and what role this has in their instruction. We interviewed 38 teachers in Kindergarten to Grade 9 classrooms from 14 schools in Newfoundland and Labrador, Canada, to obtain their understandings of critical and higher order thinking in social studies and science, and how this affects instruction and assessment. The teachers believed that higher order thinking was important for all students, and attempted to teach thinking; however, they were less sure of how they might assess thinking. The teachers indicated uncertainty about what higher order thinking means, and believed they were not well prepared to teach or assess higher order thinking. L’esprit critique et les habiletés supérieures de la pensée sont des éléments essentiels de l’éducation; pourtant, il n’est pas clair si les enseignants comprennent ces concepts ou le rôle que jouent ceux-ci dans leur enseignement. Nous avons interrogé 38 enseignants de la maternelle à la 9e année et provenant de 14 écoles à Terre-Neuve-et-Labrador, au Canada, de sorte à apprendre comment ils concevaient l’esprit critique et les habiletés supérieures de la pensée en études sociales et en science, et dans quelle mesure leur perception affectait l’enseignement et l’évaluation. Les enseignants croyaient que les habiletés supérieures de la pensée étaient importantes pour tous les élèves et ils tentaient d’enseigner la réflexion ; toutefois, ils étaient moins certains quant à la façon d’évaluer celle-ci. Les enseignants ont manifesté une incertitude quant à la définition des habiletés supérieures de la pensée et estimaient qu’ils n’étaient pas bien préparés pour les enseigner ou les évaluer.